Dream big : know what you want, why you want it, and what you're going to do about it - Goff, Bob (Nelson Books, an imprint of Thomas Nelson, 2020)
From New York Times bestselling author Bob Goff, the creator of the popular Dream Big conferences, a wildly inspiring yet utterly practical blueprint for helping readers find and reach their biggest dreams.